Total dystrophic onychomycosis due to syncephalastrum racemosum - A rare cause and its novel treatment option - Prasenjeet Mohanty; Siddhartha Dash; Liza Mohapatra; Monica Jain (Wolters Kluwer Medknow Publications, 2019)
Onychomycosis is a fungal infection of the nail caused by dermatophytic (99%) and/or non-dermatophytic (1%) (including yeasts) infections of the nailplate. Among the non-dermatophytes, the yeast Candida albicans, Candida tropicalis, and other molds like Scopulariopsis spp., Scytalidium spp., Fusarium spp., and Aspergillus spp. may be responsible. Herein, we report a case of total dystrophic onychomycosis in a 41-year-old female, caused by Syncephalastrum racemosum and its complete improvement with a combination of oral pulse itraconazole and 1064 nm Q-switched Nd-YAG laser. This case is being reported due to the rarity of causative organism for onychomycosis and a novel approach in its treatment.